ID 252 – Auditory startle reflex (ASR) in ischemic and hemorrhagic stroke. Issue 3 (March 2016) - Yagüe, S.; Veciana, M.; Pedro, J.; Cardona, P.; Quesada, H.; Kumru, H.; Flores, C.; Montero, J.; Valls-Solé, J.
Abstract : Objective: To evaluate the influence of cortical and subcortical vascular lesions on ASR. Methods: We studied in 16 patients (9 middle cerebral artery (MCA) lesions and 7 basal ganglia hematoma (BGH)): ASR, MEP, cortical silent period, H reflex and Fugl-Meyer and Ashworth scale. Six were evaluated in the acute phase, 6 in subacute and chronic phases and 4 in both. Results: Four of 5 BGH patients evaluated in the acute phase had an absent ASR and one responded only on the clinically spared side. On the contrary, four of 5 MCA patients evaluated in the acute phase presented an increased biceps response on the clinically affected side (CAS). In subacute and chronic phases 3 of 5 MCA and 4 of 5 BGH patients developed enhanced biceps responses on the CAS. Conclusions: Enhanced ASR in vascular lesions can be due to a loss of the inhibitory hemispheric or basal ganglia drive on ASR generators. The absence of ASR in the acute phase of BGH could suggest a transient hypofunction of brainstem structures. Key message: Ischemic stroke can be associated with an increased ASR on the CAS and BGH with an absent ASR in the acute phase, which is enhanced in subacute and chronic phases.